2022
DOI: 10.1111/andr.13221
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic variation in KATNAL1 non‐coding regions is involved in the susceptibility to severe phenotypes of male infertility

Abstract: Background: Previous studies in animal models evidenced that genetic mutations of KATNAL1, resulting in dysfunction of its encoded protein, lead to male infertility through disruption of microtubule remodelling and premature germ cell exfoliation.Subsequent studies in humans also suggested a possible role of KATNAL1 singlenucleotide polymorphisms in the development of male infertility as a consequence of severe spermatogenic failure. Objectives:The main objective of the present study is to evaluate the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…We found that HES7 (Hes family bHLH TF 7), as a transcriptional repressor, [ 52 ] was significantly upregulated in iNOA cells. Another key TF, SOX5, is necessary for correct gene expression patterns during spermatogenesis [ 53 ] and its expression was significantly downregulated in iNOA cells. Therefore, we speculate that the increase in HES7 transcriptional activity and decrease in SOX5 transcriptional activity may disrupt the key regulatory network during spermatogenesis and cause iNOA.…”
Section: Discussionmentioning
confidence: 99%
“…We found that HES7 (Hes family bHLH TF 7), as a transcriptional repressor, [ 52 ] was significantly upregulated in iNOA cells. Another key TF, SOX5, is necessary for correct gene expression patterns during spermatogenesis [ 53 ] and its expression was significantly downregulated in iNOA cells. Therefore, we speculate that the increase in HES7 transcriptional activity and decrease in SOX5 transcriptional activity may disrupt the key regulatory network during spermatogenesis and cause iNOA.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mutant mice [10] indicate that loss-of-function mutations in KATNAL1 disrupt MT function and can cause male infertility by affecting spermatogenesis. Subsequent human studies [11] also supported that mutations in the KATNAL1 gene may facilitate male infertility. Furthermore, Wu et al [12] also highlighted the importance of MTs-related gene defects (particularly KIF15 and dynamin 1) in azoospermia samples by using single-cell transcriptome analysis (scRNAseq).…”
Section: Introductionmentioning
confidence: 91%